The Geography of Power in Medieval Japan. - Keirstead, Thomas (Princeton legacy library., 2014)
In this reevaluation of the estate system, which has long been recognized as the central economic institution of medieval Japan, Thomas Keirstead argues that estates, or shoen, constituted more than a type of landownership. Through an examination of rent rolls, land registers, maps, and other data describing individual estates he reveals a cultural framework, one that produced and shaped meaning for residents and proprietors. Keirstead's discussion of peasant uprisings shows that the system, however, did not define a stable, closed structure, but was built upon contested terrain. Drawing on.